Longitudinal monitoring of neutral and adaptive genomic diversity in a reintroduction. Issue 4 (25th March 2022) - Marshall, Imogen R.; Brauer, Chris J.; Wedderburn, Scotte D.; Whiterod, Nick S.; Hammer, Michael P.; Barnes, Thomas C.; Attard, Catherine R. M.; Möller, Luciana M.; Beheregaray, Luciano B.
Abstract: Restoration programs in the form of ex‐situ breeding combined with reintroductions are becoming critical to counteract demographic declines and species losses. Such programs are increasingly using genetic management to improve conservation outcomes. However, the lack of long‐term monitoring of genetic indicators following reintroduction prevents assessments of the trajectory and persistence of reintroduced populations. We carried out an extensive monitoring program in the wild for a threatened small‐bodied fish (southern pygmy perch, Nannoperca australis ) to assess the long‐term genomic effects of its captive breeding and reintroduction. The species was rescued prior to its extirpation from the terminal lakes of Australia's Murray‐Darling Basin, and then used for genetically informed captive breeding and reintroductions. Subsequent annual or biannual monitoring of abundance, fitness, and occupancy over a period of 11 years, combined with postreintroduction genetic sampling, revealed survival and recruitment of reintroduced fish. Genomic analyses based on data from the original wild rescued, captive born, and reintroduced cohorts revealed low inbreeding and strong maintenance of neutral and candidate adaptive genomic diversity across multiple generations. An increasing trend in the effective population size of the reintroduced population was consistent with field monitoring data in demonstrating successful re‐establishment of the species. This provides a rare empirical example that the adaptive potential of a locally extinct population can be maintained during genetically informed ex‐situ conservation breeding and reintroduction into the wild. Strategies to improve biodiversity restoration via ex‐situ conservation should include genetic‐based captive breeding and longitudinal monitoring of standing genomic variation in reintroduced populations. Abstract : Monitoreo Longitudinal de la Diversidad Genómica Neutral y Adaptativa en una Reintroducción Marshall et al. 21‐643 Resumen: Los programas de restauración a manera de reproducción ex situ combinada con reintroducciones se están volviendo críticos para contrarrestar las declinaciones demográficas y la pérdida de especies. Dichos programas usan cada vez más la gestión genética para mejorar los resultados de conservación. Sin embargo, la falta de monitoreo a largo plazo de los indicadores genéticos posteriores a la reintroducción evita que se realicen evaluaciones de la trayectoria y la persistencia de las poblaciones reintroducidas. Se rescató un pez de talla pequeña (percha pigmea del sur [ Nannoperca australis ]) previo a su extirpación de los lagos terminales de la Cuenca Murray‐Darling en Australia para después reproducirlo en cautiverio con información genética y reintroducirlo. Realizamos monitoreos anuales o bianuales de la abundancia, aptitud y ocupación en vida silvestre durante once años, además de un muestreo genético posterior a la reintroducción. Analizamos los datos genómicos de los grupos originales rescatados, los nacidos en cautiverio y los reintroducidos. Nuestro objetivo era evaluar los efectos genómicos a largo plazo de la reproducción en cautiverio y la reintroducción de esta especie. Esto reveló baja endogamia y el sólido mantenimiento de la diversidad genómica neutral y adaptativa durante varias generaciones. Encontramos una coherencia entre la tendencia creciente en el tamaño de la población efectiva de la población reintroducida y los datos de campo que demostraron el restablecimiento exitoso de la especie. Nuestro estudio proporciona un raro ejemplo empírico de cómo el potencial adaptativo de una población localmente extinta puede mantenerse durante la reproducción de conservación ex situ genéticamente informada y su reintroducción. Las estrategias para mejorar la restauración de la biodiversidad por medio de la conservación ex situ deberían incluir la reproducción en cautiverio basada en la genética y el monitoreo longitudinal de la variación genómica actual de las poblaciones reintroducidas.